Maternal Emotional Availability Supports Child Communicative Development Regardless of Child Temperament: Findings From the FinnBrain Birth Cohort Study - Ollas-Skogster, Denise; Korja, Riikka; Yada, Akie; Mainela-Arnold, Elina; Karlsson, Hasse; Bridgett, David J.; Rautakoski, Pirkko; Karlsson, Linnea; Nolvi, Saara (WILEY, 2025)
The interplay of emotional availability (EA) and child temperament in association with early language development is understudied. We explored associations between maternal EA and infant communicative development and possible moderations by child temperament. Participants were 151 mother-child dyads from the FinnBrain Birth Cohort Study. Path models of associations between 8-month maternal EA and 14-month communicative development and moderation by infant temperament traits were created using SEM. Results show that EA positively predicted a latent variable of communicative development at 14 months. No direct longitudinal effect of EA on 30-month vocabulary was found. Child surgency/extraversion at 6 and 12 months significantly predicted 14-month communicative skills. Temperament did not moderate the association between EA and communicative development. Findings underscore the additive role of maternal caregiving and early surgency/extraversion in predicting early communicative development. The emotional aspects of parenting should be acknowledged as contributors to early communicative development in future studies.